The Criminal Law Enforcement on the Criminal Act of Employment - Arigonnanta Bagus Wicaksono; Bambang Tri Bawono; Jawade Hafidz (Universitas Islam Sultan Agung, 2022)
The aims of this research are: To find out and analyze the law enforcement of the crime of embezzlement in office. To find out and analyze the factors causing the occurrence of criminal acts of embezzlement in office. This study uses an empirical juridical approach, with descriptive analytical research specifications. The data used in this research is secondary data obtained through literature study. The method of data collection is obtained from literature study, then analyzed qualitatively. The result of this research is that the law enforcement of the crime of embezzlement in office is carried out through a penal approach, namely by means of legal remedies. Legal efforts with the penal route focus on repressive actions, namely eradication and crackdown actions to overcome the problem of criminal acts of embezzlement. Legal policies in the effort to enforce criminal law against criminal acts of embezzlement are included in social policies, namely policies or rational efforts in order to achieve public welfare.